2021
DOI: 10.3390/su13105530
|View full text |Cite
|
Sign up to set email alerts
|

Bambara Groundnut (Vigna subterranea L. Verdc): A Crop for the New Millennium, Its Genetic Diversity, and Improvements to Mitigate Future Food and Nutritional Challenges

Abstract: The world’s food and agricultural schemes have gradually fallen into an alarming state due to challenges such as high population birth rates, diverse agro-climatic zones, a lack of measures to counter global warming, severe practices of sole-culture cultivation, and asset reduction. A very high dependency on limited staple food crops is associated with repetitious diets, deprivation of food, and shortages of trace minerals, which often causes dietary sicknesses. To ensure nutritious diets worldwide, a real-wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 90 publications
(167 reference statements)
6
51
2
8
Order By: Relevance
“…Despite more diverse nutritional sources, breeding techniques for Bambara groundnut are not as advanced as those for peanut, chickpea, and soybean [ 6 ]. One of the reasons for Bambara groundnut's low yield is the usage of local landraces [ 7 ]. Khaliqi et al [ 8 ] reported that the yield of Bambara groundnut varied from 0.97 ton/ha to 3.12 ton/ha, though it has the ability to produce a higher yield up to 4 to 5 ton/ha under optimum conditions and standard cultivation procedures [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite more diverse nutritional sources, breeding techniques for Bambara groundnut are not as advanced as those for peanut, chickpea, and soybean [ 6 ]. One of the reasons for Bambara groundnut's low yield is the usage of local landraces [ 7 ]. Khaliqi et al [ 8 ] reported that the yield of Bambara groundnut varied from 0.97 ton/ha to 3.12 ton/ha, though it has the ability to produce a higher yield up to 4 to 5 ton/ha under optimum conditions and standard cultivation procedures [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, sufficient variability within the crop of interest is the main resource required to achieve a successful breeding program target for crop improvement [1]. Furthermore, sufficient knowledge of genetic variability among germplasm has important implications for the utilization, management and conservation of germplasm resources [2]. The Bambara groundnut (Vigna subterranea (L.) Verdc.)…”
Section: Introductionmentioning
confidence: 99%
“…is an underutilized crop with the potential to help meet global food requirements as an alternative food with a high nutritional content [1]. However, due to unimproved cultivars and poor cultural practices, the crop yield remained very low [2]. This crop is native to Sub-Saharan Africa, and it plays a socioeconomic role in semi-arid regions of the continent [3].…”
Section: Introductionmentioning
confidence: 99%
“…Different preparations from BGN have been shown to have medicinal properties ( Murevanhema and Jideani, 2013 ). Preparations from the leaves have been applied to infected wounds and abscess; extracts from the leaves have been applied to the eyes to cure epilepsy ( Khan et al, 2021 ) while leaf extracts pounded with that of Lanfana trifolia L. have been used as an insecticide to wash livestock ( Mkandawire, 2007 ). Venereal disease is treated by the Igbo tribe in Nigeria using the plant ( Oluwole et al, 2021 ).…”
Section: Importance Of Bambara Groundnut Cultivationmentioning
confidence: 99%
“…Water from boiled maize and BGN when drunk is used by the Luo tribe of Kenya to treat diarrhea while in Botswana, the black seeded landraces have been used to treat impotency ( Udeh et al, 2020 ). In South Africa, nausea was controlled in pregnant women who chewed and swallowed the seed ( Jideani and Jideani, 2021a ; Khan et al, 2021 ). In Ghana, pounded Bambara seeds have been used to treat skin rashes and the powder mixed with the meat of guinea fowl have been used as a treatment against diarrhea in children ( Akpalu et al, 2013 ).…”
Section: Importance Of Bambara Groundnut Cultivationmentioning
confidence: 99%